Impacts of a national recommendation on the sale of sweet products in Finnish schools – school-level factors and oral health inequalities - Anttila, Jaakko (fi=Turun yliopisto|en=University of Turku|, 2018)
The objective was to find out 1) if the national recommendation has had any effect on schools’ oral health-promoting actions, 2a) whether the school-level intermediary determinants were associated with the school-level socioeconomic position (SEP) and 2b) whether the effects of the national recommendation on schools’ intermediary determinants differed according to the school-level SEP. The study is based on two datasets independently collected from Finnish upperlevel comprehensive schools (N=970): the oral health-promoting actions (OHPA) data were collected through an online survey arranged in 2007 (n=480), 2008 (n=508), 2009 (n=593) and 2010 (n=478) and the oral health behaviour data via the national School Health Promotion Study. The combined, longitudinal dataset (n=360) used in this study was formed based on these two datasets. Aim 1 was investigated based on the schools that responded to the OHPA survey in 2007- 2009 (n=258) and both in 2007 and in 2010 (n=237). The baseline and longitudinal combined data were used to examine aims 2a and 2b, respectively. The national recommendation has influenced schools’ oral health-promoting actions: schools have decreased their sweet snack and soft drink selling to pupils. In addition, there seem to be associations between school-level intermediary determinants and the school-level SEP. The impact of the national recommendation on the sale of sweet products in schools was similar across all school-level SEP groups. Overall, the national recommendation was an effective tool to decrease sweet selling in Finnish schools without increasing inequalities in sweet selling. To eradicate the sale of sweet products altogether from Finnish schools, stricter actions such as legislation prohibiting the sale of unhealthy products in schools may be needed.

Kansallisen suosituksen vaikutukset koulujen makeanmyyntiin – koulutason tekijät ja suun terveyserot Väitöstutkimuksessa selvitettiin, 1) vaikuttiko kansallinen suositus koulujen suun terveyttä edistäviin toimiin, 2a) ovatko koulutason välilliset tekijät yhteydessä koulujen sosioekonomiseen asemaan ja 2b) vaihtelivatko kansallisen suosituksen vaikutukset välillisiin tekijöihin koulujen sosioekonomisen aseman mukaan. Tutkimuksen tietoaineisto koostui kahdesta kaikilta suomalaisilta yläkouluilta (N=970) erikseen kerätystä aineistosta: suun terveyden edistämiseen liittyviä toimia koskeva aineisto kerättiin vuosina 2007 (n=480), 2008 (n=508), 2009 (n=593) ja 2010 (n=478) kouluille järjestetyn kyselyn avulla, kun taas suun terveyteen liittyviä tapoja koskeva aineisto koostettiin Kouluterveyskyselyyn vastanneilta oppilailta. Näistä aineistoista muodostettiin yhdistetty aineisto (n=360). Ensimmäistä tutkimuskysymystä selvitettiin suun terveyden edistämiseen liittyviä toimia koskevan, vuosina 2007–2009 (n=258) sekä vuosina 2007 ja 2010 (n=237) kerätyn pitkittäisaineiston perusteella. Toisen tutkimuskysymyksen (2a) selvittämisessä käytettiin yhdistettyä aineistoa tutkimuksen lähtötilanteessa, ja kolmatta tutkimuskysymystä (2b) selvitettiin pitkittäisen yhdistetyn aineiston perusteella. Kansallisella suosituksella oli vaikutusta koulujen suun terveyttä edistäviin toimiin: koulut vähensivät makeisten ja virvoitusjuomien myyntiä. Lisäksi havaittiin, että koulutason välilliset tekijät ovat yhteydessä koulujen sosioekonomiseen asemaan. Kansallinen suositus myös vaikutti koulujen makeanmyyntiin yhtä paljon kaikissa koulujen sosioekonomisissa ryhmissä. Kansallinen suositus osoittautui tehokkaaksi työkaluksi suomalaisten yläkoulujen makeanmyynnin vähentämisen kannalta ilman, että makeanmyynnin sosioekonomiset erot olisivat lisääntyneet. Tiukempia toimia, kuten lainsäädäntöä, voidaan tarvita, jos koulujen makeanmyynti halutaan kokonaan lopettaa.